Timbre as a a means of reconstructing an ancient ritual in the XXI century chamber music of Kazakhstan (on the example of “Kamlanie”) - Бержапраков, Данияр (Pedagogy and Psychology, 2021)
The article considers the work for flute, viola and kyl-kobyz “Kamlanie” is examined in detail for the purpose of identifying new timbre solutions in the XXI century chamber music of Kazakhstan. At the present time, in the Kazakh musical science many works of composers have not been an object of special study from the point of timbre drama and the search for new musical colors. Therefore, the relevance of Kazakh music of the XXI century, which is important for the current generation of composers, musicologists and lovers of modern musical art, also increases. The main objective of this article was the idea to show timbre as the leading category, the most important element of drama, concept of the work, as well as to reveal the originality of timbre solution and performing techniques in the work “Kamlanie” by D.Berzhaprakov.